The Queerness of Art and the Foucauldian Origins of Judith Butler's Notion of Performativity : An Overview - Muhammed Shafi S. (Tattva Journal of Philosophy, 2024)
By deploying the methodology of Judith Butler's notion of Performativity, this article intends to understand the possibility of the concept of 'Queerness' beyond the possibilities of gender studies and queer theory and to develop a concept transcending the limits of identity. It is undeniable that Foucault's concept of disciplinarity is one of the major precursors of the notion of Performativity, which is a much more focused tool for what Foucault broadly devised. Both thinkers explain how a subject is a construction by power. They explain how bodies are marked, assigned, and manipulated and expose the banality with which these operations take one for granted. It is through unearthing the disciplinary aspects of Performativity in Butler and foreseeing the performative aspects of disciplinarity in Foucault that this article finds its methodological perspective. It is undeniable that disciplinarity and, as its extension, Performativity ultimately exposes the underlying ontology of identity as a 'truth effect' rather than an apriori truth. The paper critically analyses the artist's identity and the art discourse to expose the Queerness or underlying plurality of aesthetic experience using Performativity as a formative tool.